KEBIJAKAN PENGANGKATAN SEKRETARIS DESA MENJADI PEGAWAI NEGERI SIPIL DALAM MEWUJUDKAN EFEKTIVITAS PENYELENGGARAAN PEMERINTAHAN DESA DI KABUPATEN KENDAL - YUSRINA HANDAYANI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Policy on Appointment of Village Secretaries to Become Civil Servants in Realizing the Effectiveness of Village Government Organizations in Kendal District. Against the background of the emergence of controversy over the provision of the status of civil servants for the village secretary with the enactment of law Number 32 of 2004 on regional government aims to find out how the impact of the policy on appointment of the village secretary to become a civil servant, more specifically to describe the positive and negative impacts of the implementation of the provisions about the civil servant status for the village secretary. Various positive and negative impacts will appear coloring the implementation of the provisions on the status of civil servants for this village secretary that affect the effectiveness of the administration of the village against these negative impacts, anticipatory steps need to be taken so as not to cause problems when these provisions are implemented. The research method used is socio-legal research. The technique of collecting data is done by interview observation and documentation. Sampling is done by purposive sampling technique. The study states that in the implementation of the appointment of the village secretary to become a civil servant from stages I, II and III the appointment process was in accordance with Government Regulation Number 45 of 2007 so that a conclusion can be drawn that the provision of the status of civil servants for the village secretary must be believed as an effort to improve the administration of village governance , so that all parties, namely the government, village government and the community, should be able to actively participate in realizing a village that is modern, advanced and independent.